(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article shows that in Turkestan during the national awakening, enlightened educators Behbudi and Munavvarqari had a great contribution to the establishment of new schools, the introduction of new teaching methods and the training of a large group of teachers. and it speaks of the courage he showed in shaping and developing these schools.